Factors driving the halophyte rhizosphere bacterial communities in coastal salt marshes - Wang, Rumiao; Cui, Lijuan; Li, Jing; Li, Wei (Frontiers in Microbiology, 2023)
Root-associated microorganisms promote plant growth and provide protection from stresses. Halophytes are the fundamental component maintaining ecosystem functions of coastal salt marshes, however, it’s not clear how their microbiome are structured across large spatial scales. Here, we investigated the rhizosphere bacterial communities of typical coastal halophytes species (P. australis and S. salsa) in temperate and subtropical salt marshes across 1100 km in eastern China. Results showed soil nutrients (total organic carbon, dissolved organic carbon, total nitrogen, soluble sugars, organic acids) are high in temperate marsh, while root exudates (measured by metabolites expression) was significantly higher in subtropical marsh. We observed higher bacterial α diversity, more complex network structure and more negative connections in temperate salt marsh, which suggested intense competition among bacterial groups there. Variation partitioning analysis showed that climatic, edaphic and root exudates had the greatest effects on the bacteria in salt marsh, especially for abundant and moderate subcommunities. Random forest modelling further confirmed this but showed that plant species had limited effect. Taken together, our results provided novel knowledge on the biogeography of Halophytes microbiome in coastal wetlands, and can be beneficial for policy makers in decision-making on the management of coastal wetlands.